Developing & validating a measure for PR professionals’ self-efficacy - Gusau, Ahmed Lawal; Abdullah, Zulhamri; Tamam, Ezhar; Mohd Hasan, Nurul Ain (Canadian Center of Science and Education, 2017)
For the past three decades self-efficacy studies have been conducted in social science and other fields of academic endeavor. However, sufficient evidence has clearly shown that this research interest seems to neglect Public Relations (i.e. PR) discipline as there are hardly traceable works connected to this important field of study. This work therefore, represents an attempt to develop PR professionals’ self-efficacy scale to measure the ability of PR professionals in carrying out their duties. Exploratory factor analysis was conducted with PR experts and the result has shown a required factor loading for 23 out of total 24 items. Equally, the six operationalized dimensions were all consistent when confirmatory factor analysis was conducted. Similarly, discriminant and convergent validity tests which guarantees the instrument as valid for measuring Public Relations practitioners’ self-efficacy were also found to be fit.